Rhododendron Arboreum: An Overview - Pallavi Srivastava (Journal of Applied Pharmaceutical Science)
Rhododendron arboreum is an evergreen shrub or small tree with a showy display of bright red flowers. The name ‘RHODODENDRON’ is derived from the Greek word ‘RHODO’ means rose & ‘DENDRON’ means tree. Rhododendron is the national flower of Nepal & is known as (Laligurans) & the state tree of Uttarakhand. It is called ‘Burans, Bras, Buras or Barahke- phool’ in local dialect. It is widely popular for the processed juice of its flowers which have gained market popularity as rhodojuice / sharbat. The plant is found in the Himalayas from Kashmir eastwards to Nagaland. Various parts of the plant exhibited medicinal properties & is used for the treatment of various ailments. The present review is an effort to give the detailed survey of literature on its pharmacognosy, phytochemistry & pharmacological uses of the plant under study.
Keywords: Rhododendron arboreum, Burans, Pharmacognosy, Phytochemistry, Pharmacology.